A corpus-based study of corruption metaphors: the case of the Jordanian ‘Hirak’ protest movement - Ronza N. Abu Rumman (22046417) (2024)
This study examines the metaphors used to depict corrupt individuals in the context of the Jordanian Hirak protest movement during the Arab Spring (2011–2012). This analysis was conducted using the lens of a Critical Metaphor Analysis (CMA) approach. To this end, a specialized corpus of socio-political articles was built from two mainstream Jordanian newspapers: Al-Rai and Addustour. The corpus was examined using WordSmith Tools, which support Arabic data. The study reveals that several source domains were employed to represent corrupt individuals in the Jordanian socio-political discourse, namely, disease, organisms, warfare, nature, supernatural creatures, meal/kitchen, machine, fire and journey. The metaphors employed represent the great wrath of Jordanians toward widespread corruption and its effects on Jordanians and the nation at large. Additionally, these metaphors highlight Jordanians’ steadfast commitment to combatting corruption and holding those responsible for it accountable, both of which have been elevated to the top of their priority list. The study concludes that the use of negative metaphors to describe corrupt individuals in Jordanian socio-political discourse demonstrates the significant expansion of Jordanians’ freedom of expression in the backdrop of the Jordanian Hirak protest movement during the Arab Spring. Other Information Published in: Cogent Social Sciences License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/23311886.2024.2371494